Achieving excellent properties of resistance spot welded 2GPa-grade press hardened steel and galvanized DP980 steel via double-pulse - Xuefei Chen; Zhengxian Li; Dapeng Yang; Yuqian Wang; Hongliang Yi; Guangming Xie (Journal of Materials Research and Technology, 2024)
Obtaining the excellent resistance spot welding (RSW) properties of press hardened steel is a challenge due to the high strength with 2GPa-grade. In this study, the microstructure, mechanical properties of the RSW weld in 2GPa-grade PHS and galvanized DP980 steel were investigated. During the single pulse welding, the coarse columnar martensite is generated in the fusion zone (FZ). The low peak load is 13.2 kN for tensile-shear (TS) loading and 3.4 kN for cross-tension (CT) loading and the corresponding failure energy is 6.5 J and 16.7 J, respectively. The fracture mode under two loading conditions is partial thickness-partial pullout (PT-PP) mode. To enhance mechanical properties, the suitable double pulse welding was applied. Compared with that of the single pulse weld, double pulse weld has three special zones in FZ: the Re-melted FZ with columnar martensite, the recrystallization zone (RX-zone) with equiaxed martensite and the tempering zone (T-zone) with tempered columnar martensite. The peak load under the TS and CT loading is significantly improved by 39 pct and 44 pct and the failure energy for TS loading is enhanced by 38 pct and 186 pct for CT loading, respectively. The failure mode changes from the PT-PP mode to the pullout failure (PF) mode for CT loading in double pulse welds.